Medicinal chemistry : a look at how drugs are discovered - Ganguly, A. K.; Alluri, Sesha Sridevi (Boca Raton : CRC Press, 2021)
Medicinal Chemistry: A Look at How Drugs Are Discovered is written for those who are interested in learning how drugs are discovered. Compared to other books on the market, this text takes a different approach by presenting the subject on chemical reaction mechanism terms, which ideally makes the subject matter more interesting and easier to comprehend. The authors describe the drug discovery process, from advancing an initial lead to the approval process, and include drug discovery sources. Additional features: Explains medicinal chemistry on chemical mechanism terms, allowing for a more interesting and easier to comprehend text Includes valuable insights toward the various pathways taken at pharmaceutical industries in drug discoveries Improved by including questions raised and suggestions made from students in the authors' medicinal chemistry classes This book will benefit both upper level undergraduates and graduates studying in the fields of medicinal chemistry and drug discovery, as well as scientists working in the pharmaceutical industry.
Introduction to Drug Discovery. Enzyme Inhibitors. Receptor Agonists and Antagonists. Anticancer Drugs.
OCLC-licensed vendor bibliographic record.
Keywords: Pharmaceutical chemistry; Chemotherapy; MEDICAL / Pharmacology; SCIENCE / Chemistry / Organic; SCIENCE / Life Sciences / Biochemistry